PERSONALITY TRAITS OF MATTHEW LOGELIN IN THE FATHERHOOD FILM - Sabina Adia Achmad; Gita Rahmi (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study focused specifically on analyzing personality traits of Matthew Logelin in the Fatherhood film. Personality traits are aspects of a person's character that reveal how they think, act, and feel. The data's source is the film Fatherhood, and it is taken from the scenes and dialogues of the film. To examine the findings, the author used the qualitative approach and the personality characteristic theory of Paul Costa and Robert McCrae. According to the study's findings, Matthew Logelin's personality is characterized by high neuroticism, such as being moody, irritable, and worrying.